THE OPPORTUNITY AND CHALLENGES OF FOOD DIGITAL STRATEGY (JEMBER KFC CASE STUDY) - Eko Soemarjono; Doktri Agus Tapaningsih, Weni Indah (Universitas Bondowoso, 2024)
This study purpose to know the opportunity and challenges on food digital marketing strategy especially on KFC Jember outlet case. This research use qualitative methode. The analysis of this research is EFE-IFE Analysis, SWOT analysis and QSPM analysis. The result of this study is making product KFC which distinctive taste (W-T strategy). W-T Strategy is a main priority strategy. In practically, KFC must be making fried chicken on online purchase with distinctive taste.